Modelo pedagógico de educación básica elemental en la unidad educativa San Vicente de Paúl - Alvarez Inga, Silvia Carmita (2018)
The purpose of this research is to know the different pedagogical practices that are taught in the classrooms of the Educational Unit San Vicente de Paul with the children of the third year of basic education and seeks to describe the experience of teaching practice, where uses specific resources, methodology, evaluation, among others, within the process of inter-learning, which has been proposed with the endorsement of the Special Degree Unit of the Salesian Polytechnic University; we proceeded to witness directly the practice of teaching within the classroom, considering the Fundamentals of basic education, pedagogical models used by teachers in their class hours to later compare them with the models with which the 2016 curriculum is supported, teacher- learning strategies, learning activities, evaluation activities, among others. Consequently, it presents results and main conclusions of this Study case, structured from the systematization, analysis and description of the information collected through the direct observation of classes, field diary and teacher interview card. It is supported by a theoretical framework that addresses teaching practice and its fundamental pedagogical models in basic education.